Competition between relatives and the evolution of dispersal in a parasitoid wasp. - Innocent, T; Abe, J; West, SA; Reece, SE (2010)
Evolutionary theory predicts that levels of dispersal vary in response to the extent of local competition for resources and the relatedness between potential competitors. Here, we test these predictions by making use of a female dispersal dimorphism in the parasitoid wasp Melittobia australica. We show that there are two distinct female morphs, which differ in morphology, pattern of egg production, and dispersal behaviour. As predicted by theory, we found that greater competition for resources resulted in increased production of dispersing females. In contrast, we did not find support for the prediction that high relatedness between competitors increases the production of dispersing females in Melittobia. Finally, we exploit the close links between the evolutionary processes leading to selection for dispersal and for biased sex ratios to examine whether the pattern of dispersal can help distinguish between competing hypotheses for the lack of sex ratio adjustment in Melittobia.